PERANCANGAN PROYEK REST AREA DI MOJOKERTO DENGAN PENDALAMAN SENSE OF PLACE OLEH KONSULTAN ARSITEKTUR BHINNEKA ARCHITECT - Mohammad Ismail Fanani; Maureen Nuradhi (KREASI, 2023)
Regional ideals influence the value of Bhinneka Architect The company’s design. The planning project for an Integrated Rest Area is Bhinneka Architects’ final design project. Bangsal’s four main goals are to provide a rest area, boost the local economy, promote tourism and culture, and regulate land use near national highways. Local architecture describes an architectural design developed by the local climate and materials and the community’s social, cultural, and economic aspects. Election value is based on the results of the analysis carried out by the author in this report and obtained several results, namely the need for architects, the need for consultants who focus on locality, the potential of natural resources and human resources in Indonesia, as well as an increase in the percentage of infrastructure development in Indonesia. Applying locality design offers enormous potential to grow a place, particularly regarding boosting the tourism and business sectors. This depends on the possibilities of each location and traveler trends in that area. Steps that the company will take to achieve value stated in the company’s mission, which include conducting research on local content, creating design plans that highlight local values, maximizing the availability of local materials to be applied to designs, holding workshops as a form of company concern in improving Human Resources (HR), and making the most of technology’s potential as a marketing tool to help the business enter the national market.